Optic Nerve Traction During Adduction in Open Angle Glaucoma With Normal Versus Elevated Intraocular Pressure - Demer, Joseph L. (Curr Eye Res, 2019)
PURPOSE/AIM: We used magnetic resonance imaging (MRI) to investigate effects of intraocular pressure (IOP), race, and other factors on optic nerve (ON) traction in adduction, a phenomenon proposed as neuropathic in open angle glaucoma (OAG). MATERIALS AND METHODS: Thirty-five patients with OAG (26 with maximal untreated IOP ≤21mmHg, 9 with IOP >21mmHg) and 48 controls underwent axial and quasi-coronal MRI in central gaze and large (27–33°) abduction and adduction. Some underwent MRI at smaller ductions (21–28°). Effects of presence vs. absence of OAG; within OAG whether maximum IOP level was ≤21mmHg vs. >21mmHg; adduction angle; race; age; and gender on ON path length and globe translation were analyzed using generalized estimating equations to account for possible intereye correlations of individual subjects. RESULTS: Average visual field mean deviation (±standard error of mean, SEM) was −8.2±1.2 dB in OAG with normal IOP, and −6.1±1.4 in high IOP. In central gaze, ON path in OAG was significantly more redundant than in controls but in both groups the ON became significantly and almost equally straighter in small (~21°) or large (~27°) adduction than in central gaze. With progressive adduction only, globes retracted in OAG (P<0.005) but not in controls; this was only weakly related to globe size and not to IOP elevation. Globe retraction in adduction was significant only in OAG, and in that group was significantly greater in Asian than white patients (P<0.02). CONCLUSIONS: Although ON tethering in adduction is normal, progressive adduction is associated with abnormal globe retraction, in OAG regardless of IOP level. This phenomenon is more prominent in Asians who have OAG. Traction in adduction may cause repetitive strain injury to the ON and peripapillary sclera, thus contributing to the optic neuropathy of glaucoma independent of IOP.